To Wear or Not to Wear: A Commentary on Mistrust in Public Comments to CDC Tweets about Mask-Wearing during COVID19. (April 2022) - Batova, Tatiana
Trust is an important component of crisis communication, and social media has been shown a promising avenue for building trust. Yet, mixed findings about how effectively government organizations utilize social media during health crises such as pandemics or infectious disease outbreaks require further research to better understand how trust is created and destroyed. This study investigates the factors that reflect mistrust in the public comments to the CDC tweets about mask-wearing during the 3 months after the first reported case of COVID19 in the U.S. The findings show that multiple factors representing mistrust were present in the public comments. What is more, the feeling of anger was growing in the comments as the health crisis progressed, which also could have been trust-damaging.